Review xanthan gum: produksi dari substrat biomassa, variabel efektif, karakteristik dan regulasi serta aplikasi dan potensi pasar - Prabawa, I Dewa Gede Putra; Salim, Rais; Khairiah, Nadra; Ihsan, Hamlan; Lestari, Ratri Yuli (Jurnal Riset Industri Hasil Hutan, 2019)
Xanthan gum is an extracellular polysaccharide produced by a pure culture of Xanthomonas campestris through the fermentation process of carbohydrate sources in controlled conditions. These conditions must be carefully evaluated to obtain an optimal combination between yield and quality of the gum, and also production costs. The issue of this review is to provide a consolidated source of information on studies about xanthan gum production, alternative carbon sources from biomass substrates, effective variables on optimization production, characteristics, applications, and regulations status of xanthan gum. Lastly, the market potential is also discussed in this review.